2018
DOI: 10.1002/dc.23900
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of endobronchial ultrasound‐guided transbronchial needle aspiration for assessing programmed death ligand‐1 expression in nonsmall cell lung cancer

Abstract: EBUS TBNA is effective and has a high proportion of satisfactory results for testing PD-L1 expression on tumor cells in addition to NGS and ALK FISH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 20 publications
4
32
1
Order By: Relevance
“…We observed a high concordance of PD-L1 expression when cell blocks contained a greater number of viable tumor cells. Similar to our results, previous studies have also shown improved consistency of PD-L1 expression between EBUS-TBNA and biopsy specimens with increased tumor cell count [27] and cell blocks containing greater than 100 tumor cells would have satisfactory PD-L1 staining results [28]. Our study further investigated the threshold for cell block specimens to serve as a suitable surrogate for PD-L1 staining, which showed that a high rate of concordance was achieved with cutoff of tumor cells set (28-8: TC ≥400; SP142: TC ≥500).…”
Section: Discussionsupporting
confidence: 91%
“…We observed a high concordance of PD-L1 expression when cell blocks contained a greater number of viable tumor cells. Similar to our results, previous studies have also shown improved consistency of PD-L1 expression between EBUS-TBNA and biopsy specimens with increased tumor cell count [27] and cell blocks containing greater than 100 tumor cells would have satisfactory PD-L1 staining results [28]. Our study further investigated the threshold for cell block specimens to serve as a suitable surrogate for PD-L1 staining, which showed that a high rate of concordance was achieved with cutoff of tumor cells set (28-8: TC ≥400; SP142: TC ≥500).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, diagnostic yield per puncture of histological specimens obtained using the SS needle in this study (58.7%) was consistent with that reported in previous reports (57%-61.3%) [12,13]. Recent studies have shown that the specimens obtained by EBUS-TBNA are tolerable for genetic analysis, such as next generation sequencing, and immunohistochemical analysis for programmed death ligand 1 [17][18][19][20]. Obtaining proper samples with higher diagnostic yield adequate for these additive critical testing for diagnosis and treatment would be considerably beneficial, therefore, improved sampling by modifying EBUS-TBNA needles maybe clinically helpful.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have evaluated the 22C3 PharmDx assay on the Dako autostainer platform, and the SP263 on the Ventana BenchMark Ultra . Skov et al demonstrated excellent concordance (95%) between the 22C3 and 28‐8 clones on the Dako autostainer on CBs.…”
Section: Predictive Icc In Lung Cancer Cytologymentioning
confidence: 99%
“…Overestimation of PD‐L1 positivity due to nonspecific cytoplasmic staining of background macrophages and inflammatory cells can occur in both CBs and smears and can be particularly challenging in effusion samples with predominantly singly lying tumor cells admixed with inflammatory cells and mesothelial cells . A confirmatory immunostain such as TTF‐1 and/or a pan‐leucocyte marker (eg, CD45) performed on a corresponding section will aid in confirmation of tumor cells for scoring of PD‐L1 positivity …”
Section: Predictive Icc In Lung Cancer Cytologymentioning
confidence: 99%